Cilnidipine antihypertensive efficacy, pleiotropic benefits and experiences by cardiologists: findings from a digital questionnaire-based study - S. Agrawal, Pavan; N. Karande, Pratibha; J. Khobragade, Kunal (International Journal of Advances in Medicine, 2026)
Background: Cilnidipine, a fourth-generation calcium channel blocker with dual L- and N-type action, offers distinct benefits in hypertension, though varied cardiologist awareness and prescribing may limit optimal use. Methods: A cross-sectional survey was conducted among 416 practicing cardiologists across India between 17 April and 15 July 2025 to assess knowledge, perceptions, and prescribing preferences for cilnidipine in essential hypertension. A validated 20-item self-administered multiple-choice questionnaire captured mechanistic understanding and clinical perspectives following e-consent. Items addressed comparative advantages over other calcium channel blockers, effects on target organs, therapeutic applications (including combinations and patient subgroups), and metabolic benefits in metabolic syndrome. Responses were collected electronically and analyzed using descriptive statistics to summarize awareness and prescribing trends. Results: Most cardiologists (85.1%) identified cilnidipine’s dual L- and N-type blockade as its key differentiator from conventional CCBs. Over half recognized its superior nocturnal BP control (56.3%), reduced BP variability via autonomic stabilization (52.6%), and lowering of mean arterial pressure without reflex tachycardia (54.6%). A substantial proportion (64.2%) acknowledged reno-protective benefits over amlodipine, while 55.8% favored its use in elderly and resistant hypertensive patients. Notably, 61.0% recognized improved insulin sensitivity in metabolic syndrome. However, knowledge gaps remained regarding its effects on the RAAS and endothelial function. Conclusions: The survey reveals strong cardiologist awareness of cilnidipine’s sympatholytic, reno-protective, and hemodynamic benefits, alongside partial misconceptions regarding RAAS and endothelial effects. These findings underscore the need for ongoing clinical education and support cilnidipine’s role as a well-tolerated, organ-protective antihypertensive.